Iringan Musik Dalam Pantomim - Nur Iswantara (SELONDING, 2018)
Pantomime is one of the oldest theater arts, where mime artists tell something just using their body, without talking. Pantomime artists are known for their white makeup and black pigtails, as well as other facial features to exaggerate their emotions. Black and white striped tops, white gloves and black hats are also complete with traditional Pantomime artist costumes. These clothes and makeup have become a tradition of many Pantomime artists. In adding the atmosphere of the movement displayed, a music illustration is given to bring the atmosphere to life.This study uses qualitative methods and action research methods which is a reflective research method. This type of research is able to offer new ways and procedures to improve and enhance the professionalism of pantomime presentation techniques. The approach used is structural and educative. The structure approach is used to solve something related to the arrangement or building of multi-level pantomime presentations, while the educational approach is used to solve those relating to pantomime education.Music illustrations in the Pantomime show can support the atmosphere of the show. The music played can be adjusted to the theme of the movement played by a Pantomime. Keywords: Pantomime, Illustration of Music, Atmosphere.